Ukryte w języku aspekty przygotowania dzieci do szkoły - Grażyna Szyling (Problemy Wczesnej Edukacji)
In this paper I reconstruct the image of school generated by children a short while before they cross their first educational threshold. I am interested in the aspect of school readiness hidden in language, which is anchored in culture, social life and children’s experiencing of the world. The theoretical basis for the conducted analyses is the linguistic theory also known as the Sapir- Whorf hypothesis, which is complemented by the psychological concept of cognitive schemata and their role of in the process of discovering reality. The data was collected through group interviews conducted with kindergarten children focused on the issue. The language image of the schools’ world generated by children and reconstructed in the analysis conforms to the concept of transmissive education dominating in the Polish society, which positively values blind obedience and observance of other people’s instructions as the strategy of learning. The paradox is that the cognitive schemata that the children have been equipped with are suitable for what is demanded of them at the stage of early education. Their impact paralysing the development of a person can only be seen when the perspective is changed and “the school is thought of differently”.